RADIATION PHYSICS IN CANCER TREATMENT- A STUDY OF RADIOTHERAPY TECHNIQUES - Jaiswal, Shweta; Jaiswal, Ayush (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Radiation therapy plays a pivotal role in cancer treatment, utilizing advanced technologies to target and destroy cancer cells while minimizing damage to healthy tissues. This paper provides an in-depth analysis of radiotherapy techniques, including 3D Conformal Radiotherapy, Intensity-Modulated Radiotherapy (IMRT), and Proton Therapy, highlighting their mechanisms, applications, and effectiveness. The paper explores radiobiological effects, emphasizing the impact of radiation on cellular structures and tumour control, as well as challenges such as tumour heterogeneity, radio resistance, and normal tissue toxicity. With the integration of emerging technologies like artificial intelligence, the future of radiotherapy holds potential for personalized treatment plans and enhanced outcomes. Through a comprehensive discussion on current challenges and future directions, this study underscores the need for further innovation to overcome the limitations of current treatments and improve accessibility. The use of numerical data and tables reinforces key concepts, offering quantitative insights into radiotherapy's performance and its implications for cancer care. Ultimately, this paper contributes to the understanding of radiation physics in cancer treatment and presents forward-looking strategies for improving radiotherapy efficacy.